WIDE IMPLEMENTATION OF DIGITAL TECHNOLOGIES AND MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES IN EDUCATION - Khasanov Muzafar Sodikovich (Journals Park Publishing, 2024)
With the development of technology, the presence of only one computer for training using technical means remained sufficient. The computer has successfully taken over the functions previously performed by TV, VCR, film projector, slide projector and others. In addition, the quality of information transmission, storage, and imaging has increased significantly.
Keywords: information technology, computer, operating systems, networks, pedagogical software tools, virtual existence.